A DECENTRALIZED CERTIFICATE VERIFICATION SYSTEM LEVERAGING BLOCKCHAIN AND NON-FUNGIBLE TOKENS - Ge, Tivlumun; Udoji, Joel Aondofa; Adom, Isaac Terngu (FUDMA JOURNAL OF SCIENCES, 2026)
Academic certificate verification in many institutions is still carried out using centralized and manual systems, which are prone to forgery, data manipulation, high administrative costs, and delays in verification. These challenges reduce the reliability and efficiency of credential validation. This research work focuses on the development of a Decentralized Certificate Verification System (DCVS) that improves security, transparency, and trust in academic credential verification. The proposed system uses blockchain technology to represent academic certificates as Non-Fungible Tokens (NFTs) based on the ERC-721 standard deployed on the Polygon blockchain. Certificate documents and metadata are stored off-chain using the Interplanetary File System (IPFS), while cryptographic references are recorded on the blockchain to ensure data integrity and prevent tampering. The system adopts Self-Sovereign Identity (SSI) principles, allowing students to own and share their credentials while enabling employers and institutions to verify certificates without relying on a central authority. Evaluation of the system on the Polygon test network showed a reliable result with a minting confirmation time of 3.2 seconds, less than the 10-second standard benchmark, verification latency of 0.8 seconds, less than the 2-second benchmark, and a transaction cost of 0.00021 MATIC, less than the 0.01 MATIC standard cost. The study demonstrates that blockchain-based solutions can effectively address the challenges of traditional academic certificate verification systems.